Analyzing Students' Commognitive Processes in Solving Pythagorean Theorem Problems: A Gender-Based - Ain, Nur'; Lefrida, Rita; Pathuddin, Pathuddin; Alfisyahra, Alfisyahra (Jurnal Pendidikan MIPA, 2024)
This study describes students' cognitive in solving Pythagorean theorem problems in terms of gender. The research design used is explorative with a qualitative descriptive approach. The research subjects selected were 2 students, namely 1 male student and 1 female student. Data collection was carried out using written assignments and interviews. Checking the quality of the research results using data credibility is done by extending involvement, increasing persistence, discussions with peers, and membercheck and dependability. Data analysis techniques used in this research are data condensation, data display, and conclusion drawing and verification. The results showed that male and female students had raised all commognitive indicators. Male and female students can generally bring up keywords in the form of the words "area of a right triangle 25 ", "perimeter = K", and "hypotenuse c in k". Male students wrote very brief information while female students wrote clear and complete information. The description of the solution written by male and female students is different. The differences found were the use of visual mediators such as visualizing. Male students generalized a as height, b as base, c as hypotenuse while female students generalized a as base, b as height, c as hypotenuse. Endorsed narratives carried out by male and female students can write the formula for the hypotenuse of the Pythagorean theorem, the formula for the area of a right triangle, the formula for the perimeter of a right triangle and the factoring formula. Male and female students can also express the definition of the formula in solving Pythagorean theorem problems. Routines performed by male and female students can choose the right concepts and methods so that they have a good effect on the results of their solutions.       Keywords: commognitive, pythagorean theorem, gender. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1839-1853